THE ROLE OF COOPERATIVES IN IMPROVING THE RURAL ECONOMY: A LITERATURE ANALYSIS - Khusniyah; Eyad Saleh Bani-Domi; Iyad Abdallah Al- Shreifeen (CV. Adiba Aisha Amira, 2024)
Cooperatives are often regarded as the backbone of the rural economy, contributing significantly to the improvement of the socio-economic welfare of its people. The study method in this research uses the literature method. The results show that cooperatives have substantial potential to support rural economic development and diversification, but also require a strategic approach and appropriate policy support to fully realise their contribution. The conclusion of this study confirms the importance of cooperatives in accelerating rural development and calls for more effective and coordinated development efforts.